(untitled) (Computer systems and information technologies, 2022)
The environment is full of various sounds - signals registered by human and animal hearing organs, which in terms of frequency and strength merge into a monotonous, incoherent sound. The physical carriers of signals reaching the hearing organs are acoustic (sound) waves – mechanical waves that propagate in the air and are perceived by the hearing organs. Human hearing organs can perceive sounds in a fairly wide range of frequencies and intensities. The range of sounds heard by a person is limited by two threshold curves: the lower one is the threshold of perception, the upper one is the threshold of pain sensations. The human hearing threshold is 0 dB at a frequency of 1000 Hz, and the pain threshold occurs from a sound of 140 dB [2]. As long as there have been wars, it is known that mass battle cries and drumbeats oppress the enemy. The sirens of attack planes and bombers make him feel terrified and want to run away. Now an explanation has been found for this: loud sounds excite a person, contribute to the influx of a large amount of hormones into the blood, in particular, adrenaline, as a result of which there is a feeling of danger and fear [3]. There is a description of existing approaches to assess the impact of sounds on the emotional state of man, which will be the first step towards creating a model for analyzing the impact of sounds on the emotional state of man based on the theory of discrete emotions. Generated values for emotional evaluation of sounds.